Secondary school students' views of food and nutrition education in Kolkata, India. Issue 3 (3rd April 2017) - Rathi, Neha; Riddell, Lynn; Worsley, Anthony
Abstract : Purpose: School-based nutrition education programmes have the potential to reinforce healthy dietary behaviours in adolescents. The purpose of this paper is to understand the views of secondary school students in Kolkata, India, regarding the food and nutrition curriculum, food skill acquisition at school and home and barriers to learning food skills. Design/methodology/approach: The sample of 1, 026 year nine students was drawn from nine private, English-speaking secondary schools in Kolkata, India to participate in a cross-sectional, self-reported paper-based survey. Data analyses including descriptive statistics and χ 2 analyses were performed. Findings: The majority of the respondents (65.3 per cent) were female. Biology, Home Science and Life skills classes were the main places in which students acquired food and nutrition knowledge. Almost two-thirds of the respondents acknowledged the importance of acquiring food-related knowledge and skills. Approximately half (48.3 per cent) reported that the food and nutrition curriculum involved excessive memorisation while around the same proportion described the curriculum as interesting (47 per cent) and easy to comprehend (50.3 per cent). However, relatively few students said they enjoyed attending food and nutrition classes (38.7 per cent). Only a minority reported receiving food skills training, i.e. cooking skills (23 per cent), meal planning skills and food purchasing skills (12.3 per cent) at school. Despite some parental support received at home, time constraints (50.5 per cent) and lack of interest (26.3 per cent) were cited as prominent barriers to learning food skills. Practical implications: These data underscore the need for a skills-focussed food and nutrition curriculum to improve Indian adolescents' food-related skills, nutritional knowledge and dietary behaviours. Originality/value: This is the first cross-sectional survey to investigate the delivery of nutrition education and food skills in the Indian school context.